2015
DOI: 10.1007/s10144-015-0489-y
|View full text |Cite
|
Sign up to set email alerts
|

Island biogeography as a test of reproductive interference

Abstract: Theoretical studies have predicted that reproductive interference must exclude either of the interacting species, but no testing of this prediction has ever been reported for natural populations. This study surveyed the distribution patterns of herbaceous Veronica plants, including one native and three alien species, to test whether the invasion of the alien species exerting reproductive interference excluded the native species. Results showed that the native species was repeatedly excluded from islands where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…In this sense, although this study used naturally coexisting species (at a regional scale), the experimental setting was similar to (1, 1) in Table . Similar study designs can be found in other work that has observed reproductive interference between coexisting species at the regional scale (e.g., Friberg et al, ; Hochkirch, Gröning, & Bücker, ; McLain & Pratt, ; Okuzaki et al, ; Takakura & Fujii, ).…”
Section: Discussionsupporting
confidence: 79%
“…In this sense, although this study used naturally coexisting species (at a regional scale), the experimental setting was similar to (1, 1) in Table . Similar study designs can be found in other work that has observed reproductive interference between coexisting species at the regional scale (e.g., Friberg et al, ; Hochkirch, Gröning, & Bücker, ; McLain & Pratt, ; Okuzaki et al, ; Takakura & Fujii, ).…”
Section: Discussionsupporting
confidence: 79%
“…The final two contributions are empirical study reports. Takakura and Fujii (2015) report on the effect of reproductive interference on species distributions based on the field survey of biogeographic distribution patterns on various Japanese islands of four congeneric herbaceous plant species: a native species and three invasive species. They also provide evidence for habitat partitioning between the native species and an invasive species driven by reproductive interference on the Japanese main island of Honshu, where the invasive species is abundant.…”
Section: Contents Of the Special Featurementioning
confidence: 99%
“…Rarity of conspecifics also increases the likelihood and costs of reproductive interference, in which mating attempts by one species have fitness costs on reproductively isolated co‐occurring heterospecifics (Gröning and Hochkirch, , Burdfield‐Steel and Shuker, , Tastard et al., , Kyogoku, ). Negative effects of heterospecific mating pressure can reduce use of otherwise suitable habitat (Takakura and Fujii, ), may be mediated by gamete interactions that reduce fertility (Hettyey et al., ), or even cause death. Each of these effects can impact population demography (Ting and Cutter, ).…”
Section: Introductionmentioning
confidence: 99%